A case of pancreatitis, panniculitis and polyarthritis syndrome: Elucidating the pathophysiologic mechanisms of a rare condition - Ines Loverdos; Marc C. Swan; Shant Shekherdimian; Abdulrahman A. Al-Rasheed; Rayfel Schneider; Joel S. Fish; Bo-Yee Ngan; Khosrow Adeli; Mark E. Lowe; Vijay P. Singh; Wednesday Marie A. Sevilla; Jacob C. Langer; et al. (Elsevier, 2015)
Pancreatitis-Panniculitis-Polyarthritis (PPP) syndrome is rare and its physiopathology unclear. A 6-year old boy suffered of traumatic pancreatitis complicated by PPP syndrome. Extensive investigations demonstrated high levels of pancreatic lipase and fatty acids in the affected peripheral tissues. These findings support the sequence of peripheral lipolysis and fatty acid accumulation inducing tissue inflammation.